Body size, assortative mating and divorce rates in a little-known skua taxon, the Falkland Skua Stercorarius antarcticus antarcticus - Pich, Claudia (2022)
Several studies have attempted to identify the selective pressures leading to reversed size dimorphism (RSD), a characteristic of skuas and of a wide range of bird species with a raptorial lifestyle. One of the prevailing hypotheses posits that females in species of aggressive and well-armed males should select males that are smaller than themselves, to avoid injuries during pair formation and mating. This hypothesis predicts assortative mating by size in such species, and in previous research, this was confrmed to occur in two skua species. This study presents, for the frst time, biometric data for Falkland Skuas Stercorarius antarcticus antarcticus based on large sample sizes. Despite the clear RSD, we found no assortative mating by size, which could be related to the low divorce rates and few opportunities for mate selection in this population. Our results highlight the need for further work to fnd an explanatory hypothesis for the evolution and maintenance of reversed size dimorphism in skuas.